2023
DOI: 10.3390/plants12020311
|View full text |Cite
|
Sign up to set email alerts
|

Winter Green Manure Decreases Subsoil Nitrate Accumulation and Increases N Use Efficiencies of Maize Production in North China Plain

Abstract: Planting a deep-rooted green manure (GM) (more than 1.0 m depth) greatly improves soil fertility and reduces the loss of nutrients. However, few studies have examined the response of soil nitrogen (N) distribution in the soil profile and subsoil N recovery to the long-term planting and incorporation of deep-rooted GM. Based on a 12-year (2009–2021) experiment of spring maize-winter GMs rotation in the North China Plain (NCP), this study investigated the effects of different GMs that were planted over the winte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 67 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…Despite the overall good performance metrics for the modified ELEMeNT-N, it should be noted that several simulation results deviated appreciably from the measured riverine N fluxes (figures 3(b) and (c)). These discrepancies likely result from the lack of data before 1980 that prevented determination of pre-1980 nitrogen accumulation in watershed soils (Yang et al 2020, Hu et al 2023.…”
Section: Model Performancementioning
confidence: 99%
“…Despite the overall good performance metrics for the modified ELEMeNT-N, it should be noted that several simulation results deviated appreciably from the measured riverine N fluxes (figures 3(b) and (c)). These discrepancies likely result from the lack of data before 1980 that prevented determination of pre-1980 nitrogen accumulation in watershed soils (Yang et al 2020, Hu et al 2023.…”
Section: Model Performancementioning
confidence: 99%
“…Improving nutrient use efficiency-nutrient input harvested as product-is one of the most effective means of increasing crop productivity while decreasing environmental pollution [8]. Numerous studies have reported that improving nutrient utilization efficiency is closely related to agricultural management [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Intercropping leguminous green manure (LGM), such as hairy vetch, is a productive planting system that can make full use of environmental resources and respond to the low nutrient use efficiency of farmland soil in contemporary agricultural production [20]. The positive effect of legumes on crop yield has been confirmed through a large number of field experiments [10,21] and is primarily due to the improvement of N recovery from the LGM. For example, legumes can fix atmospheric N 2 [22].…”
Section: Introductionmentioning
confidence: 99%
“…Salazar et al (2021) in an experiment with maize-leguminous rotation system, have shown that the introduction of cover crops contributed to increase the NUE, but without yield gains. Hu et al (2023) have found in a long-term experiment that leguminous and non-leguminous cover crops increased the NUE by maize and also promoted better yields of the main crop.…”
Section: Introductionmentioning
confidence: 99%